Ants as Indicators of Restoration Success: Relationship with Soil Microbial Biomass in the Australian Seasonal Tropics - Andersen, Alan N.; Sparling, Graham P. (Restoration ecology, 1997)
Ants are widely used as bioindicators in Australian land assessment and monitoring programs, particularly in relation to ecosystem restoration following mining. Little is known, however, about the relationship between ant community development and key ecological processes such as nutrient cycling. We have examined the relationship between ant species richness and soil microbial biomass at 17 sites subject to disturbance by mining in the Kakadu region of Australia's Northern Territory. The number of ant species recorded ranged from 7 at an unvegetated site undergoing restoration to 43 at a site that was undisturbed except for edge effects. Soil microbial biomass ranged from 19.3 to 134.3 μgC/g. Ant species richness was positively correlated with soil microbial biomass (r= 0.638), more so than was plant species richness (r= 0.342 for total plant species, r= 0.499 for woody species only). Our findings demonstrate a correlation between aboveground ant activity and belowground decomposition processes at disturbed sites, thereby providing support for the use of ants as indicators of restoration success following disturbance. Interestingly, when a range of undisturbed sites in the region was considered, a negative rather than positive relationship between ant richness and soil microbial biomass was found. This illustrates the importance of distinguishing between variation within a habitat due to disturbance and variation across different habitats when searching for indicators of ecological change.